Rancang Bangun Sistem Informasi Tracer Study bagi Alumni Fakultas Teknik Universitas Mataram berbasis Web - Nadiyasari Agitha; Yunita Lestari; Sri Endang Anjarwani (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2021)
Tracer study or commonly known as track record study or alumni survey, is the study of graduates of higher education institutions. The Faculty of Engineering is one of the faculties at the University of Mataram. The Faculty of Engineering, University of Mataram has four departments, including the Department of Civil Engineering, the Department of Mechanical Engineering, the Department of Electrical Engineering, and the Informatics Engineering study program. Each department will graduate students in each judicial period each year. At this time, the Faculty of Engineering has conducted a tracer study for its alumni. The tracer study is usually carried out using social media such as Facebook or using Google forms. This method is considered inappropriate because the files used are not stored in one place. The design process for this information system uses Waterfal. Waterfall is a reliable method in planning which is carried out with non-repetitive iterations. Based on the results of the questionnaire testing conducted, all respondents gave a score of agree and strongly agree. With an average percentage of 48% who answered strongly agree and a percentage of 52% for those who answered agree, this information system has helped the Faculty of Engineering in carrying out tracer studies.